2008
DOI: 10.1073/pnas.0709558105
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically disordered γ-subunit of cGMP phosphodiesterase encodes functionally relevant transient secondary and tertiary structure

Abstract: The retinal phosphodiesterase (PDE6) inhibitory ␥-subunit (PDE␥) plays a central role in vertebrate phototransduction through alternate interactions with the catalytic ␣␤-subunits of PDE6 and the ␣-subunit of transducin (␣t). Detailed structural analysis of PDE␥ has been hampered by its intrinsic disorder. We present here the NMR solution structure of PDE␥, which reveals a loose fold with transient structural features resembling those seen previously in the x-ray structure of PDE␥46-87 when bound to ␣t in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
124
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(129 citation statements)
references
References 49 publications
(72 reference statements)
5
124
0
Order By: Relevance
“…4) clearly demonstrated that the additional 10 amino acids in the longer truncation mutant induced a partial inhibition of catalytic activity in the absence of the blocking C-terminal segment. This region encompasses the ␣1 helical region previously defined in structural studies (19,20). Furthermore, the ability of the region comprising amino acids 71-76 to further increase the inhibition of cGMP hydrolysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4) clearly demonstrated that the additional 10 amino acids in the longer truncation mutant induced a partial inhibition of catalytic activity in the absence of the blocking C-terminal segment. This region encompasses the ␣1 helical region previously defined in structural studies (19,20). Furthermore, the ability of the region comprising amino acids 71-76 to further increase the inhibition of cGMP hydrolysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The proline-rich and polycationic region (amino acids 18 -45, open box) serves as the primary interaction site with the GAF domains of the PDE6 catalytic dimer. The C-terminal domain of P␥ (amino acids ϳ62-87) is shown as consisting of three ␣-helical sequences (␣1, light gray; ␣2, dark gray; ␣3, black) based on structural studies of its complex with transducin ␣-subunit (20) or free in solution (19); the functional interaction of these putative structural elements with PDE6 catalytic dimer is a focus of the experiments in this paper. B, some of the P␥ truncation mutants and synthetic peptides used in this study are depicted.…”
Section: The C-terminal Region Of P␥ Is a Classical Noncompetitive Inmentioning
confidence: 99%
See 1 more Smart Citation
“…For PDE5, cGMP-induced activation is mediated by binding to the most N-terminal, GAF-A, domain, whereas for PDE2 cGMP interacts with GAF-B, which is more proximal to the catalytic domain. PDE6 is also regulated by cGMP binding to GAF-A, in the unique context of interaction with the P␥ subunit (19,20). The physiological role of GAF domain regulation for PDE10 and 11 is still to be determined (21).…”
mentioning
confidence: 99%
“…However, the intrinsically disordered PDE␥, especially its N-terminal half (18), has been problematic in solving a crystal structure of ␣t and RGS9⅐␤5 bound with the full-length PDE␥. As indicated in our previous reports (13,19,20), the label transfer approach has allowed for systematic mapping of interactions between fulllength molecules, thus circumventing the problems of intrinsic disorder that can impede efforts in solving atomic structures.…”
mentioning
confidence: 99%